The Potential of Blockchain Technology in the Financial Industry - Rahmadani Rahmadani; Indra Marto Silaban (International Journal of Information System and Innovative Technology, 2025)
Blockchain technology has emerged as a revolutionary solution across various industries, with its potential being particularly recognised in the financial sector. This research aims to explore blockchain technology in the financial industry, focusing on its role in improving transparency, security, and efficiency in financial transactions. A decentralised data management technique, blockchain will eliminate intermediaries, reduce transaction costs, and provide a secure and immutable ledger to increase trust among financial stakeholders. This research will also highlight key areas where blockchain is transforming the financial system, such as cryptocurrencies, smart contracts, and decentralised finance (DeFi). The research also discusses the opportunities and challenges faced by the financial industry in adopting blockchain, including regulatory issues, scalability concerns, and integration with existing infrastructure. Through a comprehensive review of current trends, case studies, and theoretical frameworks, this research aims to offer insights into the future potential of blockchain technology on the financial industry, so that the long-term benefits of blockchain adoption can result in a more efficient, transparent, and secure global financial ecosystem.